Are Entrepreneurs Aware of Covered Interest Parity and Dollar Shortage? - Farhad Nariman; Almas Heshmati (Institute of Labor Economics (IZA), 2022)
The purpose of this study is demonstrating why entrepreneurs should monitor the broad dollar index. This paper explains the reason why the broad dollar index has become a risk (leverage) gauge since 2008 using the Covered Interest Parity (CIP). CIP can be viewed as a reflection of the shadow price of a bank's balance sheet, which reflects how risky the situation is for a certain entrepreneur attempting to start a new venture. The importance of the link between banks and entrepreneurs has long been recognized. When the banking system is constrained, an entrepreneur should be informed. Entrepreneurs will be able to understand the circumstances in which they want to succeed more correctly if they are aware of the state of the banking system. Overall, the risk appetite of the banking system is critical for both traditional and export-oriented businesses. The VIX index (Chicago Board Options Exchange market volatility index) was once employed as a barometer of the banking system's risk appetite, but things have changed since the great financial crisis and the index has been supplanted by the broad dollar index. Since 2008, the broad dollar index has been used as an indicator of a bank's risk appetite. This paper provides entrepreneurs a handy index for assessing the economic conditions in which they choose to be entrepreneurs more accurately.
Keywords: F31; F34; F41; G02; G21; 330; dollar shortage; entrepreneurship; balance sheet capacity; dollar index; covered interest parity